Central power and local power: socio-imaginary dispute during Covid-19 (Revista Iberoamericana de Estudios Municipales, 2023)
During Covid-19 in Chile, the presidential power, centralized and instituted, made a series of decisions that were not fully accepted in the territory. Thus, the mayors, local and institutional power, implemented their own mitigation measures. The objective of the article is to show how the health crisis promoted plans and decisions of various municipalities that achieved greater plausibility, compared to the central government’s proposals. An analysis is carried out on news texts, letters from mayors and presidential speeches regarding the measure to suspend school classes to prevent the spread of the virus. It was detected that the social imaginary about power changes, where the legitimacy and plausibility of local power is greater than that of the central government.
Keywords: central power; local power; social imaginary; Covid-19; chilean democracy